Human transcendence: the possibility of spiritual irredentism. Issue 2 (March 2019) - Tallis, Raymond
The article is concerned with the project of spiritual irredentism; of reclaiming for humanity that which has been donated to God. It takes its rise from the view, particularly associated with Feuerbach and Durkheim, that the object of religious worship is a projection of humanity's intuition of its own transcendence. The broad outlines of the manner in which mankind transcends nature are sketched. The question then remains as to how this is to be placed at the service of humanity, and, indeed, to meeting those needs that religion has served. This is the greatest challenge of secular humanism.